School Principals as Leaders in Fostering Attitudes of Religious Tolerance in Schools - Sjeddie Rianne Watung; Sunarno Sunarno; Alfina Wildatul Fitriyah; Nanda Saputra; Yulianto Abas (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
The aim of this research is to find out the role of the principal of Santo Yusuf Middle School in building an attitude of religious tolerance using a qualitative research approach. The current era of globalization and increasing cases of religious intolerance in educational institutions make this research even more important to be discussed as a solution and recommendation for school principals to optimize their leadership roles in the educational institutions they lead. This research method uses in-depth interview techniques with key informants, namely the school principal and supporting informants, namely Muslim and non-Muslim teachers. The findings of this research found that the role of the principal has a significant influence on the success of building an attitude of tolerance in schools by mobilizing the school community with the initiative to create internal guidelines, directing by equalizing mutually agreed perceptions, guiding in an accommodating manner and being a good role model, protecting rights. school community through assimilation and development programs through internal routine programs and interfaith cultural programs. This finding is also an additional option for school principals in increasing the values ​​of tolerance in schools as well as strengthening that the important role of school principals has a significant impact on the conduciveness of the work environment and improving the quality of education at large. Conduciveness through an appropriate humanitarian approach will influence the development of holistic potential students both intellectually, socially, emotionally, and spiritually, with that the potential risk of intolerance at school can be prevented and overcome.